Interaction Between Prematurity and the MAOA Gene on Mental Development in Children: A Longitudinal View - Yao, Nai-Jia; Hsieh, Wu-Shiun; Lin, Chyi-Her; Tseng, Ching-Ing; Lin, Wan-Yu; Kuo, Po-Hsiu; Yu, Yen-Ting; Chen, Wei J.; Jeng, Suh-Fang (Frontiers in Pediatrics, 2020)
This study aimed to examine the association of dopamine-related genes with mental and motor development and the gene-environment interaction in preterm and term children. A total of 201 preterm and 111 term children were examined for their development at 6, 12, 18, 24, and 36 months and were genotyped for 15 single-nucleotide polymorphisms (SNPs) in dopamine-related genes (DRD2, DRD3, DAT1, COMT, and MAOA). An independent sample of 256 preterm children was used for replication. Since the developmental age trends of preterm children differed from those of term children, the analyses were stratified by prematurity. Among the 8 SNPs on the MAOA gene examined in the whole learning sample, the results of linkage disequilibrium analysis indicated that they were located in one block (all D′ > 0.9), and rs2239448 was chosen as the tag (r2 > 0.85). In the analysis of individual SNPs in each dopamine-related gene, the tag SNP (rs2239448) in MAOA remained significantly associated with the mental scores of preterm children for the interaction with age trend (p < 0.0001; largest effect size of 0.65 at 24 months) after Bonferroni correction for multiple testing. Similar findings for rs2239448 were replicated in the independent sample (p = 0.026). However, none of the SNPs were associated with the motor scores of preterm children, and none were related to the mental or motor scores of term children. The genetic variants of the MAOA gene exert influence on mental development throughout early childhood for preterm, but not term, children.